2021
DOI: 10.1111/ijcp.14489
|View full text |Cite|
|
Sign up to set email alerts
|

A cross‐sectional study on prescribing and dispensing errors at a corporate hospital in South India

Abstract: Background The substantial and increasing use of medications escalating the risk of harm globally. The serious medication errors in hospital and community settings resulting from patient injury and death. Hence, a cross‐sectional study was aimed to analyse the prescribing and dispensing errors in the outpatient departments of a south Indian hospital. Materials and methods A prospective cross‐sectional study was carried out to evaluate the prescribing, and dispensing errors in outpatients who seek patient couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…There are 37 articles that discuss the incidence of MEs and their factors in Asia, where the articles consist of 9 articles from Southeast Asia [10][11][12][13][14][15][16][17][18] ; 3 articles from East Asia [19][20][21] ; 7 articles from South Asia [22][23][24][25][26][27][28] and 18 articles from West Asia [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . A total of 2 articles discuss the incidence of MEs and their factors in Australia [47][48] .…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are 37 articles that discuss the incidence of MEs and their factors in Asia, where the articles consist of 9 articles from Southeast Asia [10][11][12][13][14][15][16][17][18] ; 3 articles from East Asia [19][20][21] ; 7 articles from South Asia [22][23][24][25][26][27][28] and 18 articles from West Asia [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . A total of 2 articles discuss the incidence of MEs and their factors in Australia [47][48] .…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The term "dispensing error" refers to a discrepancy between a prescription and the medication that the pharmacy distributes to the patient or the ward based on this prescription, including the dispensing of a medicine with lower pharmaceutical or informational quality 31 . There are 14 studies reported wrong drug including into dispensing errors 17,21,23,25,[31][32][33][34][35][36][39][40][43][44]49 , so wrong dose is the most common type of errors. In addition, wrong dose is also included in dispensing errors.…”
Section: Dispensing Errorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article by Kandasamy et al, 1 the funding information of ‘This work was supported by the Deanship of Scientific Research at King Khalid University, Abha, Kingdom of Saudi Arabia, with project number GRP 339’ was incomplete and it should read as ‘This work was supported by the Deanship of Scientific Research at King Khalid University, Abha, Kingdom of Saudi Arabia, with project number GRP/339/42.…”
mentioning
confidence: 99%